Paraneoplastic cerebellar degeneration as a manifestation of metastatic recurrent carcinoma breast: rare scenario. (27th August 2018) - Saha, Shivangi; Kumar, Atish; Kumar, Chitresh; Kataria, Kamal
Abstract : Carcinoma breast presenting with paraneoplastic cerebellar degeneration is a rare scenario. We report a case of a 52-year-old woman, which is a follow-up case of completely treated carcinoma breast presenting with paraneoplastic cerebellar degeneration which, on investigation, revealed metastatic disease with recurrence at previous scar site and metastasis to contralateral axilla. The patient was given pulse methyl prednisolone therapy and underwent wide local excision of nodule and right axillary lymph node dissection with 14 cycles of trastuzumab and paclitaxel as adjuvant therapy. However, there was no detectable change in neurological symptoms at 6-month follow-up postoperatively. This case report highlights the need for clinicians to be aware of all possible presentations of carcinoma breast and its recurrence, including rare manifestations as in this case.